NUMERICAL SIMULATION OF SHEAR STRENGTH TESTING ON STRING BAMBOO - Prawreddhi Nugraha, Aulia
Bamboo is a common commodity in the archipelago of Indonesia. Its wide range of use is its virtuous quality. From consuming it on the dinner table to the more cost-efficient alternative for construction, bamboo is valued. String bamboo is a bamboo species available within the islands, widely used for furniture and handicrafts. Due to its nature, bamboo mechanical properties also vary, between species, within the species, and even from different sections of the bamboo itself.